PENGARUH PEMBIAYAAN AKAD MUDHARABAH, MURABAHAH, DAN MUSYARAKAH TERHADAP NISBAH BANK SYARIAH INDONESIA TAHUN 2022 - 2024 - Muhamad Ibrahim Ilham; Karsam; Rina Pratiwi (Universitas La Tansa Mashiro, 2025)
This study aims to determine the effect of Mudharabah, Murabahah, Musyarakah financing on the profitability of case studies at Bank Syariah Indoensia 2022-2024 period. In this study, there are three independent variables, namely Mudharabah, Murabahah, Musyarakah financing. And the dependent variable in this study is profitability. Population and sample in this study Bank Syariah Indonesia. The data collection method used is documentation with reference to the bank's annual financialstatements by Bank Syariah Indonesia official website. The data analysis technique used in this study is simple linear regression. The results of the research simultaneously state that the financing of Mudharabah, Murabahah, Musyarakah, has a positive and significant effect on profitability. Meanwhile, partially Mudharabah financing has a negative and significant effect on profitability. Murabahah and Musyarakah financing has a positive and significant effect on profitability.